ANALISIS KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN(Z-SCORE) STUDI KASUS DI PERUSAHAAN TELEKOMUNIKASI - Silaban, Pasaman (Jurnal Akuntansi, 2014)
The objective of this research is to analyse a company’s bancruptcy by the use of Altman Z-Score model. This study used the descriptive quantitative analysis method. The data used are secondary data, the annual financial statements and income statements of each company. Data were analyzed using four X ratio defined by Altman and were used to calculate the Z score of each company in order to determine its health level. The analysis shows that in 2010 - 2012 the company's health condition was not good. In 2010 the company was in the gray zone, then the next year the company's condition declined, and in 2012 it was at an unhealthy condition/bankrupt. Telkom is in a healthy state and has increased each year, Indosat is in the unhealthy zone with Z score tends to increase every year. By knowing the health condition of a company, corporate management is able to evaluate each financial ratio and fix the company's financial performance in order to survive and compete.